Polarizing plate and method for manufacturing the same
A polarizer with controlled moisture permeability and absorbance, combined with a retardation layer, stabilizes warpage in image display devices, addressing manufacturing defects by regulating moisture distribution.
Patent Information
- Application Number
- JP2021055019
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-29
- Publication Date
- 2025-02-10
- Estimated Expiration
- 2041-03-29
AI Technical Summary
Polarizers used in image display devices are prone to warping, which can lead to manufacturing defects due to environmental changes, and existing solutions do not adequately stabilize the warpage state.
A polarizer with specific moisture permeability and absorbance properties, combined with a retardation layer, is manufactured using a moisture-regulating treatment to stabilize warpage, involving protective layers made of cycloolefin and cellulosic resins, and a retardation layer composed of oriented liquid crystal compounds.
The solution results in a polarizing plate with stable warpage, reducing manufacturing defects in image display devices by controlling moisture absorption and distribution, thereby maintaining consistent performance.
Smart Images

Figure 0007628452000009 
Figure 0007628452000010 
Figure 0007628452000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizing plate and a method for producing a polarizing plate. [Background technology]
[0002] Image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices, inorganic EL display devices), are rapidly becoming widespread. A polarizing plate is typically used in the image display panel mounted on the image display device. In practice, a polarizing plate with a retardation layer, in which a polarizing plate and a retardation plate are integrated, is widely used (e.g., Patent Document 1). However, polarizing plates have a problem in that they are prone to warping, and the direction and degree of warping are prone to change depending on the environment in which they are placed. This warping and change in warping can cause, for example, manufacturing defects in image display devices. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 3325560 Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention has been made to solve the above-mentioned problems in the conventional art, and a main object of the present invention is to provide a polarizing plate in which the warping state is stabilized. [Means for solving the problem]
[0005] According to an embodiment of the present invention, there is provided a polarizing plate having a moisture permeability of 40 g / m at 40° C. and 92% RH. 2 - A first protective layer for 24 hours or less, a polarizer, and a moisture permeability of 350g / m2 at 40°C and 92% RH 2A second protective layer having a durability of 24 hours or more, in this order, and an absorbance measured with an infrared moisture content meter of 0.0100 or more and 0.0155 or less. In one embodiment, the first protective layer contains a cycloolefin resin. In one embodiment, the second protective layer comprises a cellulose-based resin. According to another embodiment of the present invention, there is provided a polarizing plate with a retardation layer, the polarizing plate having the above polarizing plate and a retardation layer disposed on the second protective layer side of the polarizing plate. In one embodiment, the retardation layer is a layer in which a liquid crystal compound is aligned and fixed.
[0006] According to yet another embodiment of the present invention, there is provided a method for producing a polarizing plate, the method comprising the steps of: 2 - A first protective layer for 24 hours or less, a polarizer, and a moisture permeability of 350g / m2 at 40°C and 92% RH 2 and a second protective layer having a durability of 24 hours or more, in this order, and subjecting the laminate to a moisture conditioning treatment, thereby obtaining a polarizing plate having an absorbance of 0.0100 or more and 0.0155 or less as measured with an infrared moisture meter. In one embodiment, the humidity conditioning treatment is performed in a state where one main surface of the second protective layer is exposed. According to yet another embodiment of the present invention, there is provided a method for producing a polarizing plate with a retardation layer, comprising laminating a retardation layer on the second protective layer side of the polarizing plate obtained by the above-mentioned production method. Effect of the Invention
[0007] According to the embodiment of the present invention, by satisfying a predetermined absorbance, it is possible to obtain a polarizing plate in which the warping state is stabilized. [Brief description of the drawings]
[0008] [Figure 1] 1 is a schematic cross-sectional view showing an outline of a configuration of a retardation layer-attached polarizing plate according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing an example of a laminate before being subjected to a humidity conditioning treatment. [Diagram 3] FIG. 4 is a cross-sectional view showing an example of a warped state of a polarizing plate. [Figure 4] 1 is a schematic cross-sectional view showing an outline of an image display panel according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0010] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.
[0011] A. Polarizing plate with retardation layer FIG. 1 is a schematic cross-sectional view showing an outline of a retardation layer-attached polarizing plate according to one embodiment of the present invention. The retardation layer-attached polarizing plate 100 has a polarizing plate 10, a retardation layer 20, and a protective film 30 in this order. The polarizer 11 has a first main surface 11a and a second main surface 11b facing each other, and a first protective layer 12 is arranged on the first main surface 11a side (typically, the viewing side) of the polarizer 11, and a second protective layer 13 is arranged on the second main surface 11b side of the polarizer 11. Specifically, the polarizing plate 10 includes the polarizer 11, the first protective layer 12 arranged on one side of the polarizer 11 (the side on which the retardation layer 20 is not arranged), and the second protective layer 13 arranged on the other side of the polarizer 11 (between the polarizer 11 and the retardation layer 20). The retardation layer 20 has a laminated structure including a first retardation layer 21 and a second retardation layer 22.
[0012] In the illustrated example, the retardation layer 20 has a laminated structure including a first retardation layer 21 and a second retardation layer 22. However, unlike the illustrated example, the retardation layer 20 may have a laminated structure of three or more layers, or may be a single layer.
[0013] Although not shown, the retardation layer-attached polarizing plate may further have other functional layers. The type, characteristics, number, combination, arrangement, etc. of the functional layers that the retardation layer-attached polarizing plate may have may be appropriately set according to the purpose. For example, the retardation layer-attached polarizing plate may further have a conductive layer or a conductive layer-attached isotropic substrate. A retardation layer-attached polarizing plate having a conductive layer or a conductive layer-attached isotropic substrate is applied to, for example, a so-called inner touch panel type input display device in which a touch sensor is incorporated inside an image display panel. As another example, the retardation layer-attached polarizing plate may further have other retardation layers. The optical characteristics (e.g., refractive index characteristics, in-plane retardation, Nz coefficient, photoelastic coefficient), thickness, arrangement, etc. of the other retardation layers may be appropriately set according to the purpose. As a specific example, the viewing side of the polarizer may be provided with other retardation layers (typically, a layer that imparts (elliptical) polarizing function, a layer that imparts ultra-high retardation). By having such a layer, excellent visibility can be realized even when the display screen is viewed through polarizing lenses such as polarized sunglasses, etc. Therefore, a retardation layer-attached polarizing plate having such a layer can be suitably applied to an image display device that can be used outdoors.
[0014] Each member constituting the retardation layer polarizing plate may be laminated via any suitable adhesive layer (not shown). Specific examples of the adhesive layer include an adhesive layer and a pressure-sensitive adhesive layer. Specifically, the retardation layer 20 may be bonded to the second protective layer 13 via an adhesive layer (preferably using an active energy ray curable adhesive), or may be bonded to the second protective layer 13 via a pressure-sensitive adhesive layer (e.g., an acrylic pressure-sensitive adhesive). As shown in the figure, when the retardation layer 20 has a laminated structure of two or more layers, the retardation layers are bonded to each other, for example, via an adhesive layer (preferably using an active energy ray curable adhesive).
[0015] For example, the protective film 30 is attached to the retardation layer 20 via an adhesive layer. In practice, this adhesive layer allows the retardation layer-attached polarizing plate 100 to be attached to an image display panel body. The protective film 30 can function as a release film (separator) that is temporarily attached until the retardation layer-attached polarizing plate 100 is used. By temporarily attaching the protective film, for example, the adhesive layer is protected and the retardation layer-attached polarizing plate can be formed into a roll.
[0016] The retardation layer-attached polarizing plate may be in a long shape or a sheet shape. Here, "long" refers to a long and narrow shape whose length is sufficiently long relative to its width, for example, whose length is 10 times or more, preferably 20 times or more, relative to its width. The long retardation layer polarizing plate can be wound into a roll.
[0017] A-1. Polarizing plate The polarizing plate includes a polarizer, a first protective layer, and a second protective layer. The thickness of the polarizing plate is preferably 20 μm or more, more preferably 25 μm or more. On the other hand, the thickness of the polarizing plate is preferably 70 μm or less, more preferably 65 μm or less. In addition, when an adhesive layer is used when laminating the polarizer and the protective layer, the thickness of the adhesive layer is not included in the thickness of the polarizing plate.
[0018] The absorbance of the polarizing plate 10 (the laminated portion from the first protective layer 12 to the second protective layer 13) measured with an infrared moisture content meter is 0.0100 or more, and preferably 0.0105 or more. Meanwhile, the absorbance of the polarizing plate 10 is 0.0155 or less, and preferably 0.0150 or less. By satisfying such an absorbance, a polarizing plate with a stabilized warpage state can be obtained.
[0019] The polarizer is typically a resin film containing a dichroic substance (e.g., iodine). Examples of the resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films.
[0020] The thickness of the polarizer is preferably 18 μm or less, more preferably 15 μm or less, and further preferably 12 μm or less, while the thickness of the polarizer is preferably 1 μm or more.
[0021] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is, for example, 41.5% to 46.0%, preferably 42.0% to 46.0%, and more preferably 44.5% to 46.0%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more.
[0022] The protective layer may be formed of any suitable film that can be used as a protective layer for a polarizer. Specific examples of the material that is the main component of the film include cellulose-based resins such as triacetyl cellulose (TAC), polyester-based, polyvinyl alcohol-based, polycarbonate-based, polyamide-based, polyimide-based, polyethersulfone-based, polysulfone-based, polystyrene-based, cycloolefin-based such as polynorbornene, polyolefin-based, (meth)acrylic-based, acetate-based, and other transparent resins.
[0023] The retardation layer-attached polarizing plate according to the embodiment of the present invention is typically disposed on the viewing side of an image display device, and the first protective layer 12 is disposed on the viewing side. Therefore, the first protective layer 12 may be subjected to surface treatment such as hard coat (HC) treatment, anti-reflection treatment, anti-sticking treatment, and anti-glare treatment, as necessary.
[0024] The thickness of the protective layer is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and further preferably 15 μm to 35 μm. When the above-mentioned surface treatment is performed, the thickness of the first protective layer 12 includes the thickness of the surface treatment layer.
[0025] The second protective layer 13 disposed between the polarizer 11 and the retardation layer 20 is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm and the retardation Rth(550) in the thickness direction is -10 nm to +10 nm. The thickness of the protective layer disposed between the polarizer 11 and the retardation layer 20 is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and further preferably 10 μm to 30 μm.
[0026] In one embodiment, the first protective layer 12 has a moisture permeability of 40 g / m at 40° C. and 92% RH. 2 The second protective layer 13 has a moisture permeability of 350 g / m 2 24 hours or more. According to such an embodiment, the above-mentioned absorbance can be satisfactorily achieved. Specifically, the moisture conditioning treatment described below can cause the polarizer 11 to absorb moisture from the second protective layer 13 side, and the moisture taken into the polarizer 11 (polarizing plate 10) can be prevented from being released from the first protective layer 12 side. In addition, the polarizer 11 can have an excellent water absorption rate (water retention capacity), so that the moisture once taken into the polarizer 11 is unlikely to escape.
[0027] The moisture permeability of the first protective layer 12 at 40° C. and 92% RH is preferably 30 g / m 2 - 24h or less, preferably 20g / m 2 On the other hand, the moisture permeability of the first protective layer 12 at 40° C. and 92% RH is, for example, 1 g / m 2 24 hours or more. Examples of the material of the first protective layer 12 include cycloolefin resins and polyester resins. When the above-mentioned surface treatment is performed, the moisture permeability of the first protective layer 12 is measured including the surface treatment layer.
[0028] The moisture permeability of the second protective layer 13 at 40° C. and 92% RH is preferably 500 g / m 2 - 24h or more, preferably 600g / m 2On the other hand, the moisture permeability of the second protective layer 13 at 40° C. and 92% RH is, for example, 1200 g / m 2 The life span is 24 hours or less. Examples of the material for the second protective layer 13 include cellulose-based resins such as TAC, polycarbonate-based resins, and (meth)acrylic-based resins.
[0029] The polarizing plate may be produced by any suitable method. Specifically, the polarizing plate may include a polarizer produced from a single-layer resin film, or may include a polarizer obtained by using a laminate of two or more layers.
[0030] The method for producing a polarizer from the above-mentioned single-layer resin film typically includes subjecting the resin film to a dyeing treatment using a dichroic substance such as iodine or a dichroic dye, and a stretching treatment. As the resin film, for example, a hydrophilic polymer film such as a polyvinyl alcohol (PVA) film, a partially formalized PVA film, or an ethylene-vinyl acetate copolymer partially saponified film is used. The method may further include an insolubilization treatment, a swelling treatment, a crosslinking treatment, or the like. A polarizing plate can be obtained by laminating a protective layer on at least one side of the obtained polarizer. Such a production method is well known and commonly used in the art, and therefore a detailed description thereof will be omitted.
[0031] The polarizer obtained by using the laminate can be produced, for example, by using a laminate of a resin substrate and a resin film or resin layer (typically, a PVA-based resin layer). Specifically, the laminate can be produced by applying a PVA-based resin solution to a resin substrate, drying the resin substrate to form a PVA-based resin layer on the resin substrate, and obtaining a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, preferably, a PVA-based resin layer containing a halide and a PVA-based resin is formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution and stretching it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95°C or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, preferably, the laminate is subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. Typically, the manufacturing method of this embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of PVA, and high optical properties can be achieved. In addition, by simultaneously increasing the orientation of PVA in advance, problems such as a decrease in the orientation of PVA and dissolution can be prevented when immersed in water in the subsequent dyeing and stretching steps, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation disorder and the decrease in orientation of the PVA molecules can be suppressed compared to when the PVA-based resin layer does not contain a halide, and high optical properties can be achieved. Furthermore, by shrinking the laminate in the width direction by the drying shrinkage treatment, high optical properties can be achieved. The obtained resin substrate / polarizer laminate may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or any suitable protective layer may be laminated on the peeled surface of the resin substrate / polarizer laminate after peeling the resin substrate from the resin substrate / polarizer laminate, or on the surface opposite to the peeled surface, depending on the purpose. Details of the method for producing such a polarizer are described in, for example, JP2012-73580A and JP6470455A. The entire disclosures of these publications are incorporated herein by reference.
[0032] A polarizing plate satisfying the above-mentioned predetermined absorbance can be obtained, for example, by preparing a laminate of a first protective layer, a polarizer, and a second protective layer, and subjecting this laminate to a moisture conditioning treatment (typically, a humidification treatment). By subjecting such a laminate to a moisture conditioning treatment (for example, before laminating a retardation layer), the absorbance (moisture content) of the obtained polarizing plate can be easily controlled. Specifically, the polarizer can be efficiently absorbed with moisture, and the polarizer can be easily controlled so that it has an equilibrium moisture content. In one embodiment, a polarizing plate satisfying a desired absorbance (moisture content) is obtained by adjusting the conditions of the moisture conditioning treatment according to the absorbance (moisture content) of the laminate. The equilibrium moisture content refers to the weight fraction of moisture when the laminate is left in an atmosphere of constant temperature and constant humidity until the moisture content does not change substantially.
[0033] 2 is a cross-sectional view showing an example of a laminate before being subjected to a humidity conditioning treatment. The laminate 90 has a first protective layer 12, a polarizer 11, a second protective layer 13, and a surface protective film 40 in this order. The surface protective film 40 typically includes a substrate (not shown) and a pressure-sensitive adhesive layer formed on one side of the substrate, and is peelably attached to the main surface 13a of the second protective layer 13. The substrate of the surface protective film 40 is made of, for example, a polyester-based polymer such as polyethylene terephthalate (PET). The thickness of the surface protective film 40 is, for example, 30 μm to 100 μm.
[0034] Although not shown, it is preferable to perform a humidity conditioning treatment on the laminate 90 in a state in which the surface protective film 40 is peeled off and the main surface 13a of one side (the side on which the polarizer 11 is not arranged) of the second protective layer 13 is exposed. According to such an embodiment, the above-mentioned absorbance can be satisfactorily achieved. Specifically, in the humidity conditioning treatment, moisture can be efficiently absorbed (moisture is diffused) from the second protective layer 13 side into the polarizer 11, and the time for the humidity conditioning treatment can be shortened.
[0035] The humidity conditioning is preferably performed by placing the laminate in an environment of 23°C to 40°C and 60% RH to 95% RH. For example, when the temperature is 23°C, the laminate is placed in an environment with a relative humidity of 60% RH or more. For example, when the temperature is 35°C, the laminate is placed in an environment with a relative humidity of 60% RH or more. For example, when the temperature is 40°C, the laminate is placed in an environment with a relative humidity of 60% RH or more. By performing humidity conditioning in such an environment, problems such as a deteriorated polarizing plate being obtained or condensation occurring on the polarizing plate after humidity conditioning, which causes a defective appearance, can be suppressed. The upper limit of the relative humidity can be, for example, 100% RH.
[0036] The amount of water vapor during the humidity control treatment is preferably 12 g / m 3 ~49g / m 3 and more preferably 16 g / m 3 ~40g / m 3 It is.
[0037] The time for the humidity conditioning treatment is preferably 2 to 25 minutes, and more preferably 17 minutes or less. The humidity conditioning treatment for the laminate can be accomplished in a short period of time.
[0038] After the humidity conditioning treatment, a retardation layer may be laminated on one of the main surfaces 13a of the second protective layer 13. Before laminating the retardation layer, it is preferable to again attach a surface protective film to the exposed surface 13a of the second protective layer 13 in a peelable state. According to such an embodiment, the moisture contained in the second protective layer 13 can be efficiently diffused to the polarizer 11. In addition, it is possible to prevent the moisture taken in the polarizing plate 10 from being released from the second protective layer 13 side. As described above, the polarizer 11 has a high water absorption rate, which can be higher than the water absorption rates of the first protective layer 12 and the second protective layer 13. Therefore, the moisture taken in the polarizing plate 10 may be mainly present in the polarizer 11.
[0039] The moisture permeability of the surface protection film laminated after the humidity conditioning process at 40°C and 92% RH is 40g / m 2 - 24h or less is preferable, and 20g / m2 On the other hand, the moisture permeability of the surface protection film at 40°C and 92% RH is, for example, 7 g / m 2 -24 hours or more.
[0040] The obtained polarizing plate (laminate after humidity conditioning treatment) may be warped. FIG. 3 is a cross-sectional view showing an example of the warped state of the polarizing plate. In FIG. 3, hatching is omitted from the cross section of the polarizing plate to make the drawing easier to see. In the example shown in FIG. 3, the polarizing plate 10 has a convex warp toward the second protective layer 13 side. The warp tends to occur along the absorption axis direction of the polarizing plate 10 (polarizer 11). Even if the polarizing plate is warped (even if the warp varies), the warp generated in the polarizing plate can be corrected, for example, when laminating a retardation layer, etc., which will be described later. As a result, a retardation layer-attached polarizing plate can be manufactured with a good yield.
[0041] A-2. Retardation layer The thickness of the retardation layer depends on its structure (whether it is a single layer or has a laminated structure), but is preferably 10 μm or less, more preferably 8 μm or less, and even more preferably 7 μm or less. On the other hand, the thickness of the retardation layer is, for example, 1 μm or more. In addition, when the retardation layer has a laminated structure, the "thickness of the retardation layer" means the total thickness of each retardation layer. Specifically, the "thickness of the retardation layer" does not include the thickness of the adhesive layer.
[0042] As the retardation layer, a liquid crystal compound alignment solidified layer (liquid crystal alignment solidified layer) is preferably used. By using a liquid crystal compound, for example, the difference between nx and ny of the obtained retardation layer can be significantly increased compared to non-liquid crystal materials, so that the thickness of the retardation layer for obtaining a desired in-plane retardation can be significantly reduced. Therefore, a polarizing plate with a retardation layer can be significantly thinned. In this specification, the "alignment solidified layer" refers to a layer in which a liquid crystal compound is aligned in a predetermined direction within the layer and the alignment state is fixed. The "alignment solidified layer" is a concept that includes an alignment hardened layer obtained by hardening a liquid crystal monomer as described later. In the retardation layer, typically, rod-shaped liquid crystal compounds are aligned in the slow axis direction of the retardation layer (homogeneous alignment).
[0043] The liquid crystal alignment solidified layer can be formed by performing an alignment treatment on the surface of a predetermined substrate, applying a coating liquid containing a liquid crystal compound to the surface to align the liquid crystal compound in a direction corresponding to the alignment treatment, and fixing the alignment state. Any appropriate alignment treatment can be adopted as the alignment treatment. Specifically, mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment can be mentioned. Specific examples of mechanical alignment treatment include rubbing treatment and stretching treatment. Specific examples of physical alignment treatment include magnetic field alignment treatment and electric field alignment treatment. Specific examples of chemical alignment treatment include oblique deposition method and photoalignment treatment. As the treatment conditions of various alignment treatments, any appropriate conditions can be adopted depending on the purpose.
[0044] The alignment of the liquid crystal compound is performed by treating the liquid crystal compound at a temperature at which the liquid crystal compound exhibits a liquid crystal phase according to the type of liquid crystal compound. By performing such temperature treatment, the liquid crystal compound takes on a liquid crystal state and is aligned according to the alignment treatment direction of the substrate surface.
[0045] In one embodiment, the alignment state is fixed by cooling the liquid crystal compound aligned as described above. When the liquid crystal compound is a polymerizable monomer or a crosslinkable monomer, the alignment state is fixed by subjecting the liquid crystal compound aligned as described above to a polymerization treatment or a crosslinking treatment.
[0046] Specific examples of the liquid crystal compound and details of the method for forming the alignment solidified layer are described in JP-A-2006-163343, the disclosure of which is incorporated herein by reference.
[0047] As described above, the retardation layer may be a single layer or may have a laminated structure of two or more layers.
[0048] Unlike the illustrated example, in one embodiment in which the retardation layer is a single layer, the retardation layer can function as a λ / 4 plate. Specifically, Re(550) of the retardation layer is preferably 100 nm to 180 nm, more preferably 110 nm to 170 nm, and further preferably 110 nm to 160 nm. The thickness of the retardation layer can be adjusted so as to obtain a desired in-plane retardation of the λ / 4 plate. When the retardation layer is the above-mentioned liquid crystal alignment solidified layer, the thickness is, for example, 1.0 μm to 2.5 μm. In this embodiment, the angle between the slow axis of the retardation layer and the absorption axis of the polarizer is preferably 40° to 50°, more preferably 42° to 48°, and further preferably 44° to 46°. In addition, the retardation layer preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light.
[0049] In another embodiment in which the retardation layer is a single layer, the retardation layer can function as a λ / 2 plate. Specifically, the Re(550) of the retardation layer is preferably 200 nm to 300 nm, more preferably 230 nm to 290 nm, and further preferably 230 nm to 280 nm. The thickness of the retardation layer can be adjusted so as to obtain a desired in-plane retardation of the λ / 2 plate. When the retardation layer is the above-mentioned liquid crystal alignment solidified layer, the thickness is, for example, 2.0 μm to 4.0 μm. In this embodiment, the angle between the slow axis of the retardation layer and the absorption axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and further preferably 12° to 16°.
[0050] As shown in the figure, in one embodiment in which the retardation layer 20 has a laminated structure, the retardation layer 20 has a two-layer laminated structure in which a first retardation layer (H layer) 21 and a second retardation layer (Q layer) 22 are arranged in this order from the polarizing plate 10 side. The H layer can typically function as a λ / 2 plate, and the Q layer can typically function as a λ / 4 plate. Specifically, the Re(550) of the H layer is preferably 200 nm to 300 nm, more preferably 220 nm to 290 nm, and further preferably 230 nm to 280 nm; the Re(550) of the Q layer is preferably 100 nm to 180 nm, more preferably 110 nm to 170 nm, and further preferably 110 nm to 150 nm. The thickness of the H layer can be adjusted so as to obtain a desired in-plane retardation of the λ / 2 plate. When the H layer is the above-mentioned liquid crystal alignment solidified layer, the thickness is, for example, 2.0 μm to 4.0 μm. The thickness of the Q layer can be adjusted so as to obtain a desired in-plane retardation of the λ / 4 plate. When the Q layer is the above-mentioned liquid crystal alignment solidified layer, its thickness is, for example, 1.0 μm to 2.5 μm. In this embodiment, the angle between the slow axis of the H layer and the absorption axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and even more preferably 12° to 16°; the angle between the slow axis of the Q layer and the absorption axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and even more preferably 72° to 76°. The arrangement order of the H layer and the Q layer may be reversed, and the angle between the slow axis of the H layer and the absorption axis of the polarizer and the angle between the slow axis of the Q layer and the absorption axis of the polarizer may be reversed. Furthermore, each layer (e.g., the H layer and the Q layer) may exhibit an inverse dispersion wavelength characteristic in which the phase difference value increases according to the wavelength of the measurement light, may exhibit a positive wavelength dispersion characteristic in which the phase difference value decreases according to the wavelength of the measurement light, or may exhibit a flat wavelength dispersion characteristic in which the phase difference value changes very little depending on the wavelength of the measurement light.
[0051] The retardation layer (when having a laminated structure, at least one layer) typically exhibits a refractive index characteristic of nx > ny = nz. Note that "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny > nz or ny < nz may occur. The Nz coefficient of the retardation layer is preferably 0.9 to 1.5, more preferably 0.9 to 1.3.
[0052] As described above, the retardation layer is preferably a liquid crystal alignment solidified layer. Examples of the liquid crystal compound include liquid crystal compounds (nematic liquid crystals) in which the liquid crystal phase is a nematic phase. As such liquid crystal compounds, for example, liquid crystal polymers and liquid crystal monomers can be used. The mechanism for the manifestation of liquid crystallinity of the liquid crystal compound may be either lyotropic or thermotropic. The liquid crystal polymer and the liquid crystal monomer may be used alone or in combination.
[0053] When the liquid crystal compound is a liquid crystal monomer, the liquid crystal monomer is preferably a polymerizable monomer and a crosslinkable monomer. This is because the alignment state of the liquid crystal monomer can be fixed by polymerizing or crosslinking (i.e., curing) the liquid crystal monomer. After the liquid crystal monomer is aligned, for example, if the liquid crystal monomers are polymerized or crosslinked with each other, the alignment state can be fixed thereby. Here, a polymer is formed by polymerization, and a three-dimensional network structure is formed by crosslinking, but these are non-liquid crystalline. Therefore, in the formed retardation layer, for example, a transition from a liquid crystal phase, a glass phase, or a crystal phase due to a temperature change peculiar to the liquid crystalline compound does not occur. As a result, the retardation layer becomes an extremely stable retardation layer that is not affected by temperature changes.
[0054] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on its type. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.
[0055] Any suitable liquid crystal monomer can be used as the liquid crystal monomer. For example, the polymerizable mesogen compounds described in JP-A-2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445 can be used. Specific examples of such polymerizable mesogen compounds include BASF's product name LC242, Merck's product name E7, and Wacker-Chem's product name LC-Sillicon-CC3767. As the liquid crystal monomer, a nematic liquid crystal monomer is preferable.
[0056] In another embodiment, the retardation layer 20 has a laminated structure of a first retardation layer 21 capable of functioning as a λ / 4 plate and a second retardation layer 22 (so-called positive C plate) whose refractive index characteristics show the relationship nz>nx=ny. The details of the λ / 4 plate are as described above. In this embodiment, the angle between the slow axis of the first retardation layer and the absorption axis of the polarizer is preferably 40° to 50°, more preferably 42° to 48°, and further preferably 44° to 46°. In addition, it is preferable that the first retardation layer shows an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light.
[0057] The thickness direction retardation Rth(550) of the positive C plate is preferably -50nm to -300nm, more preferably -70nm to -250nm, further preferably -90nm to -200nm, and particularly preferably -100nm to -180nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. The in-plane retardation Re(550) of the positive C plate is, for example, less than 10nm.
[0058] The second retardation layer having a refractive index characteristic of nz>nx=ny may be formed of any suitable material, but is preferably made of a film containing a liquid crystal material fixed in homeotropic alignment. The liquid crystal material (liquid crystal compound) that can be homeotropically aligned may be a liquid crystal monomer or a liquid crystal polymer. Specific examples of the liquid crystal compound and the method of forming the retardation layer include the liquid crystal compound and the method of forming the retardation layer described in
[0020] to
[0028] of JP-A-2002-333642. In this case, the thickness of the second retardation layer is preferably 0.5 μm to 5 μm.
[0059] A-3.Protection film The protective film 30 may be made of any suitable plastic film. Specific examples of the plastic film include a polyethylene terephthalate (PET) film, a polyethylene film, and a polypropylene film. As described above, the protective film 30 may function as a separator. Specifically, a plastic film whose surface is coated with a release agent is preferably used as the protective film 30. Specific examples of the release agent include a silicone-based release agent, a fluorine-based release agent, and a long-chain alkyl acrylate-based release agent.
[0060] The moisture permeability of the protective film at 40℃ and 92% RH is 40g / m 2 - 24h or less is preferable, and 20g / m 2 On the other hand, the moisture permeability of the protective film at 40°C and 92% RH is, for example, 4 g / m 2 -24 hours or more.
[0061] The thickness of the protective film is preferably 20 μm to 80 μm, and more preferably 35 μm to 55 μm.
[0062] A-4. Preparation of polarizing plate with retardation layer The retardation layer-attached polarizing plate according to the embodiment of the present invention can be obtained by laminating the above polarizing plate and the above retardation layer.
[0063] The polarizing plate and the retardation layer are laminated, for example, while they are being transported by rolls (so-called roll-to-roll). The lamination is typically performed by transferring a liquid crystal alignment solidified layer formed on a substrate. As shown in the figure, when the retardation layer has a laminated structure, each retardation layer may be laminated (transferred) sequentially onto the polarizing plate, or a laminate in which retardation layers are laminated together in advance may be laminated (transferred) onto the polarizing plate.
[0064] In one embodiment, the transfer is performed using an active energy ray curable adhesive. The thickness of the active energy ray curable adhesive after curing (thickness of the adhesive layer) is preferably 0.4 μm or more, more preferably 0.4 μm to 3.0 μm, and even more preferably 0.6 μm to 1.5 μm. In another embodiment, the transfer is performed using a pressure-sensitive adhesive. The thickness of the pressure-sensitive adhesive layer formed between the polarizing plate and the retardation layer is preferably 1 μm or more, more preferably 1 μm to 10 μm, and even more preferably 2 μm to 8 μm.
[0065] As described above, when the retardation layer-attached polarizing plate further has the protective film and the other functional layers (e.g., conductive layer, other retardation layers), these may be laminated or formed at a predetermined position by any appropriate method. For example, the protective film 30 is laminated on the retardation layer 20 side of the laminate obtained by laminating the polarizing plate 10 and the retardation layer 20, using an adhesive. The thickness of this adhesive (the thickness of the adhesive layer disposed between the retardation layer 20 and the protective film 30) is, for example, 10 μm to 40 μm.
[0066] For example, when the laminate obtained by laminating the polarizing plate 10 and the retardation layer 20 without performing the humidity conditioning treatment on the laminate of the first protective layer, the polarizer, and the second protective layer is subjected to the humidity conditioning treatment (typically, humidification treatment), depending on the configuration of the laminate, problems such as a long time required for the polarizer to absorb moisture, the polarizer not absorbing moisture sufficiently, and large variation in the moisture absorption state may occur. As a result, it is difficult to stabilize the warped state of the obtained retardation layer-attached polarizing plate, which tends to lead to manufacturing defects of the image display device. As described above, by performing the humidity conditioning treatment on the laminate of the first protective layer, the polarizer, and the second protective layer to prepare a polarizing plate that satisfies a predetermined absorbance, the warped state can be easily stabilized by the humidity conditioning treatment for a short time.
[0067] B. Image display panel The retardation layer-attached polarizing plate can be applied to an image display panel (for example, an organic EL panel). Therefore, an image display panel according to an embodiment of the present invention has the retardation layer-attached polarizing plate.
[0068] 4 is a schematic cross-sectional view showing an outline of an image display panel according to one embodiment of the present invention. In an image display panel 200, a retardation layer-attached polarizing plate 100 is arranged such that its retardation layer 20 is closer to an image display panel body 150 than the polarizing plate 10. Specifically, the retardation layer-attached polarizing plate 100 is attached to the image display panel body 150 via an adhesive layer (not shown).
[0069] When the retardation layer-attached polarizing plate 100 (polarizing plate 10) is warped, the image display panel 200 obtained by laminating it on the image display panel body 150 may also be warped. The direction (unevenness direction) and degree of warping of the retardation layer-attached polarizing plate 100 (polarizing plate 10) may be reflected in the direction and degree of warping of the obtained image display panel 200. A warped image display panel may cause manufacturing defects in image display devices. A polarizing plate in which the warped state is stabilized may reduce manufacturing defects in image display devices. EXAMPLES
[0070] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The thickness and moisture permeability are values measured by the following measuring methods. Furthermore, unless otherwise specified, "parts" and "%" in the examples and comparative examples are based on weight. 1. Thickness The thickness of 10 μm or less was measured using a scanning electron microscope (manufactured by JEOL, product name "JSM-7100F"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C"). 2. Moisture permeability (water vapor permeability) The moisture permeability was measured by a differential pressure gas chromatography method in accordance with JIS K7129-4 and ISO15106-4 (differential pressure method) using a vapor transmission rate measuring device (manufactured by GTR Tech Co., Ltd., product name "Gas transmission rate and moisture permeability measuring device"). Specifically, the moisture permeability (unit: g / m) was measured under the conditions of a temperature of 40°C, a humidity of 92% RH on the water vapor supply side, and a vacuum on the permeation side. 2 -24h) was measured.
[0071] [Example 1] (Preparation of polarizing plate) A long roll of 30 μm thick polyvinyl alcohol (PVA) resin film (Kuraray, product name "PE3000") was stretched uniaxially in the longitudinal direction by a roll stretching machine to 5.9 times its original length while simultaneously undergoing swelling, dyeing, crosslinking, and washing processes in that order, and finally drying, resulting in a moisture permeability of 350 g / m 2 A polarizer with a thickness of 12 μm was produced for 24 h. The above swelling treatment was performed by stretching the film 2.2 times while treating with pure water at 20°C. Next, the dyeing treatment was performed by stretching the film 1.4 times while treating in an aqueous solution at 30°C in which the weight ratio of iodine to potassium iodide was 1:7, with the iodine concentration adjusted so that the single transmittance of the resulting polarizer was 45.0%. Next, the crosslinking treatment was performed in two stages, and the first stage was stretched 1.2 times while treating in an aqueous solution at 40°C in which boric acid and potassium iodide were dissolved. The aqueous solution in the first stage crosslinking treatment had a boric acid content of 5.0% by weight and a potassium iodide content of 3.0% by weight. The second stage crosslinking treatment was performed by stretching the film 1.6 times while treating in an aqueous solution at 65°C in which boric acid and potassium iodide were dissolved. The aqueous solution in the second stage crosslinking treatment had a boric acid content of 4.3% by weight and a potassium iodide content of 5.0% by weight. Next, the film was washed with an aqueous potassium iodide solution at 20° C. The aqueous solution used for the washing treatment had a potassium iodide content of 2.6% by weight. Finally, the film was dried at 70° C. for 5 minutes to obtain a polarizer.
[0072] On one side of the polarizer, an HC-COP film (moisture permeability 1.6 g / m2) was attached via a polyvinyl alcohol adhesive. 2 A TAC film (moisture permeability 810 g / m2 with Re(550) of 0 nm) was then attached to the other side of the polarizer. 2 24h, thickness 20 μm) was attached as a second protective layer to obtain a laminate having a structure of HC-COP film (first protective layer) / polarizer / TAC film (second protective layer).
[0073] The obtained laminate was subjected to a humidity conditioning treatment. The humidity conditioning treatment was carried out by subjecting the laminate to a temperature of 35°C and 80% RH (water vapor amount of 32 g / m) while transporting the laminate with rolls. 3 ) for 2 minutes. In this way, a polarizing plate was obtained.
[0074] (storage) A surface protective film (moisture permeability 15 g / m2) was applied to the TAC film side of the obtained polarizing plate. 2 24h, thickness 38μm) was laminated, and in this state the polarizing plate was placed at 23℃ and 55% RH (water vapor amount 11g / m 3 ) for 30 days. The surface protection film is a film in which a pressure-sensitive adhesive layer (thickness 10 μm) is formed on a PET film (thickness 28 μm).
[0075] (Preparation of Retardation Layer) A composition was obtained by mixing 42 parts by weight of a polymerizable liquid crystal compound (L-1), 42 parts by weight of a polymerizable liquid crystal compound (L-2), 16 parts by weight of a polymerizable liquid crystal compound (L-3), 0.5 parts by weight of a polymerization initiator (PI-1), 0.09 parts by weight of a polymer (T-1), 0.04 parts by weight of a polymer (T-2), and 235 parts by weight of cyclopentanone. The composition obtained was applied onto a TAC film (substrate) on which an alignment film had been formed to form a coating film, and the coating film formed was heated to 180°C, then cooled to 120°C, and 100 mJ / cm was applied at a wavelength of 365 nm using a high-pressure mercury lamp under a nitrogen atmosphere. 2 The coating was irradiated with ultraviolet light of 1000 nm to form a liquid crystal alignment solidified layer A (thickness: 2.3 μm) on the substrate. The in-plane retardation Re(550) of the obtained liquid crystal alignment solidified layer A was 140 nm, and Re(450) / Re(550) was 0.87.
[0076] Polymerizable liquid crystal compound (L-1) [ka]
[0077] Polymerizable liquid crystal compound (L-2) [ka]
[0078] Polymerizable liquid crystal compound (L-3) [ka]
[0079] Polymerization initiator (PI-1) [ka]
[0080] Polymer (T-1) [ka]
[0081] Polymer (T-2) [ka]
[0082] A liquid crystal coating solution was prepared by dissolving 20 parts by weight of a side-chain liquid crystal polymer represented by the following chemical formula (1) (the numbers 65 and 35 in the formula indicate the mole percent of the monomer unit, and are conveniently represented as a block polymer: weight average molecular weight 5000), 80 parts by weight of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: trade name Paliocolor LC242), and 5 parts by weight of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: trade name Irgacure 907) in 200 parts by weight of cyclopentanone. The coating solution was then applied to a PET substrate that had been subjected to a vertical alignment treatment using a bar coater, and the liquid crystal was aligned by heating and drying at 80°C for 4 minutes. The liquid crystal layer was irradiated with ultraviolet light to harden the liquid crystal layer, thereby forming a liquid crystal alignment solidified layer B (thickness 3 μm) exhibiting a refractive index characteristic of nz>nx=ny on the substrate. [ka]
[0083] (Preparation of polarizing plate with retardation layer) The obtained liquid crystal alignment solidified layer A and liquid crystal alignment solidified layer B were transferred in this order to the TAC film side of the polarizing plate before storage. At this time, the transfer (lamination) was performed so that the angle between the absorption axis of the polarizer and the slow axis of the liquid crystal alignment solidified layer A was 45°. The liquid crystal alignment solidified layer A was transferred to the polarizing plate via a pressure-sensitive adhesive layer (acrylic, thickness 5 μm). Next, the liquid crystal alignment solidified layer B was transferred to the liquid crystal alignment solidified layer A via a UV-curable adhesive (thickness 1 μm). The transfer (lamination) was performed while transporting with a roll. In this way, a polarizing plate with a retardation layer was obtained.
[0084] (storage) A separator (PET film, thickness 38 μm) was attached to the retardation layer side of the obtained retardation layer-attached polarizing plate via an adhesive layer (acrylic, thickness 26 μm), and the retardation layer-attached polarizing plate in this state was placed at 23°C and 55% RH (water vapor amount 11 g / m 3 ) environment for 30 days.
[0085] [Example 2] When preparing the polarizing plate, the laminate was subjected to humidity conditioning at 35°C and 80% RH (water vapor amount 32 g / m 3 ) for 4 minutes, the same procedure as in Example 1 was carried out to obtain a polarizing plate with a retardation layer.
[0086] [Example 3] When preparing the polarizing plate, the laminate was subjected to humidity conditioning at 35°C and 80% RH (water vapor amount 32 g / m 3 ) for 7 minutes, the same procedure as in Example 1 was carried out to obtain a polarizing plate with a retardation layer.
[0087] [Example 4] When preparing the polarizing plate, the laminate was subjected to humidity conditioning at 35°C and 80% RH (water vapor amount 32 g / m 3 ) for 10 minutes, the same procedure as in Example 1 was carried out to obtain a polarizing plate with a retardation layer.
[0088] [Example 5] When preparing the polarizing plate, the laminate was subjected to humidity conditioning at 35°C and 80% RH (water vapor amount 32 g / m 3 ) for 14 minutes, the same procedure as in Example 1 was carried out to obtain a polarizing plate with a retardation layer.
[0089] [Example 6] When preparing the polarizing plate, the laminate was subjected to humidity conditioning at 35°C and 80% RH (water vapor amount 32 g / m 3 ) for 17 minutes, the same procedure as in Example 1 was carried out to obtain a polarizing plate with a retardation layer.
[0090] [Comparative Example 1] When preparing the polarizing plate, the laminate was subjected to humidity conditioning at 35°C and 80% RH (water vapor amount 32 g / m 3 ) for 34 minutes, the same procedure as in Example 1 was carried out to obtain a polarizing plate with a retardation layer.
[0091] [Comparative Example 2] When preparing the polarizing plate, the laminate was subjected to humidity conditioning at 35°C and 80% RH (water vapor amount 32 g / m 3 ) for 1 minute, the same procedure as in Example 1 was carried out to obtain a polarizing plate with a retardation layer.
[0092] The following evaluations were carried out for the Examples and Comparative Examples. The evaluation results are summarized in Table 1. <Evaluation> 1. Absorbance In the examples and comparative examples, the absorbance of the laminate, the polarizing plate and the polarizing plate with a retardation layer before and after storage (for the polarizing plate with a retardation layer, the polarizing plate obtained by removing the laminated portion from the adhesive layer with a thickness of 5 μm to the separator) was measured using a diffuse reflection type infrared moisture meter (manufactured by Kurabo Industries, product name "RM-300") to evaluate the moisture content. Specifically, in an environment of 23°C and 55% RH, members other than the laminated portion of the HC-COP film / polarizer / TAC film (surface protection film, adhesive layer, retardation layer, separator, etc.) were peeled off to prepare a measurement sample, and the measurement sample was set so that the absorption axis of the polarizer was parallel to the optical path of the infrared light and measured. 2. Change in warpage In the examples and comparative examples, the change in warpage of the polarizing plate and the polarizing plate with a retardation layer before and after storage was measured. Specifically, a test piece of 160 mm x 80 mm size was cut out from the polarizing plate before and after storage (for the polarizing plate with a retardation layer, the polarizing plate obtained by removing the laminated portion from the adhesive layer with a thickness of 5 μm to the separator). At this time, the cut-out test piece was cut out so that the direction of the long side was 45° to the absorption axis direction of the polarizer. The height of the highest part from the plane when the cut-out test piece was placed on a plane so that the TAC film side was the plane side was measured to measure the warpage, and the change in warpage before and after storage was obtained. Here, the warpage convex toward the surface on which it was placed was designated as "positive (+)", and the warpage convex toward the opposite side to the surface on which it was placed was designated as "negative (-)".
[0093] [Table 1]
[0094] In the examples, it is seen that the change in absorbance before and after storage is small, and the warpage state of the polarizing plate is stable.
[0095] [Reference example] A liquid crystal alignment solidified layer A obtained in the same manner as in Example 1 was transferred to a laminate obtained in the same manner as in Example 1, and then a liquid crystal alignment solidified layer B obtained in the same manner as in Example 1 was laminated thereon. In this state (with the PET substrate of the liquid crystal alignment solidified layer B not peeled off), the liquid crystal alignment solidified layer A was heated at 35°C and 80% RH (with a water vapor content of 32 g / m 3 ) for 10 minutes for humidity conditioning, but as in the above examples, the absorbance did not change due to the humidity conditioning. In addition, a liquid crystal alignment solidified layer A obtained in the same manner as in Example 1 was transferred to a laminate obtained in the same manner as in Example 1, and then a liquid crystal alignment solidified layer B obtained in the same manner as in Example 1 except that a TAC substrate was used as the substrate was laminated thereon. In this state (with the TAC substrate of the liquid crystal alignment solidified layer B not peeled off), the laminate was subjected to a test at 35°C and 80% RH (water vapor amount of 32 g / m 3) environment for 10 minutes, the absorbance immediately after the humidity conditioning was unchanged from before the humidity conditioning, but after 5 days had passed since the humidity conditioning (storage for 5 days), the absorbance began to increase and the warping also changed. Thus, it took time for the warping to stabilize. [Industrial Applicability]
[0096] The polarizing plate according to the embodiment of the present invention is used as a polarizing plate of an image display device, and may also be used in a curved, bendable, foldable, or rollable image display device. Representative examples of the image display device include a liquid crystal display device, an organic EL display device, and an inorganic EL display device. [Explanation of symbols]
[0097] 10 Polarizing plate 11 Polarizer 12 First protective layer 13 Second protective layer 20 Retardation layer 21 First retardation layer 22 Second retardation layer 30 Protective Film 100 Polarizing plate with retardation layer
Claims
1. Moisture permeability at 40°C and 92% RH is 40g / m 2 A first protective layer for 24 hours or less, a polarizer, and a moisture permeability of 350 g / m at 40°C and 92% RH 2 a second protective layer having a duration of at least 24 h; and subjecting the laminate to a humidity conditioning treatment; The humidity conditioning treatment is performed in a state where one main surface of the second protective layer is exposed, Obtain a polarizing plate having an absorbance of 0.0100 to 0.0155 as measured by an infrared moisture content meter. A method for manufacturing a polarizing plate.
2. The method for producing a polarizing plate according to claim 1 , wherein the first protective layer contains a cycloolefin resin.
3. The method for producing a polarizing plate according to claim 1 , wherein the second protective layer contains a cellulose-based resin.
4. The method for manufacturing a polarizing plate described in claim 1, wherein the humidity adjustment treatment is performed by placing the laminate in an environment of 23°C to 40°C and 60% RH to 95% RH.
5. The method for manufacturing a polarizing plate described in claim 1, wherein the humidity adjustment treatment time is 2 to 25 minutes.
6. A method for producing a polarizing plate with a retardation layer, comprising laminating a retardation layer on the second protective layer side of the polarizing plate obtained by the production method according to claim 1 .
7. The method for producing a polarizing plate with a retardation layer according to claim 6 , wherein the retardation layer is a layer in which a liquid crystal compound is aligned and solidified.
Citation Information
Patent Citations
Manufacturing method for polarizing plate, polarizing plate and picture display device using the polarizing plate
JP2005309394A
Polarizing plates and liquid crystal display devices
JP2008529038A
Method of manufacturing polarizing plate
JP2009244914A
Polarization plate having retardation layer and picture display unit using the same
JP2021026086A
Retardation film and optical device using the same
JP3325560B2